Crescimento e desenvolvimento da cultura da soja submetida a diferentes doses de Ascophyllum nodosum (L.) Le Jolis - Trombetta, Joana Arsego (2024)
In Brazil, soybean cultivation is the agricultural activity that has grown the most in recent years. Soy plays an important role in agricultural systems. Crop productivity has been increasing, but new technologies are needed to enhance production, such as the use of biostimulants based on algae extracts. In this sense, the general objective of this study was to characterize the effect of Ascophyllum nodosum algae extract on seed quality, growth and development and grain productivity of soybean crops. An experiment was conducted in the laboratory with seeds of cultivars DM 5958 IPRO and DM 56I59 IPRO treated with products based on A. nodosum algae, namely Bioalgas®, Phylgreen®, Acadian® and Phosamco Bio®. The treated seeds and an untreated sample were stored and seed quality tests were carried out at 0, 15, 30, 45 and 60 days after storage. Among other characteristics, seed vigor and germination, seedling size and mass were obtained. A second experiment was conducted in the field and aerial applications were carried out with products based on the algae A. nodosum (Acadian®, Phosamco Bio®, Bioalgas® and Phylgreen®) in two applications in the V4 and R1 phenological stages and in three applications in the phenological tests V4, R1 and R4, using the soybean cultivar NS5505I2X. After the first application, plants were collected weekly and the plant height and green mass of the plant were obtained and, at the time of harvest, the productivity of grains and their components were obtained. It was found that products based on A. nodosum, used in seed treatment, do not alter the quality of the seeds throughout storage and this in turn alters the quality of the seeds, reducing vigor, germination, and seedling size. Seed quality is not affected using A. nodosum based products in seed treatment. Applications of commercial liquid extracts of A. nodosum algae provide greater growth and greater mass in plants when applied foliarly. Products based on A. nodosum algae (Acadian®, Phosamco Bio®, Bioalgas® and Phylgreene®) applied to the aerial part increase grain productivity in soybeans. Two Phosamco Bio® applications provided superiority to all characteristics evaluated in the experiment.